“ ARTIFICIAL INTELLIGENCE (AI) AND ITS ROLE IN THE PROCESS OF RESOLVING INTERNATIONAL COMMERCIAL DISPUTES THROUGH ARBITRATION COURTS ” - Asatullaev Nigmatilla Ziyodulla (Scholar Express Journals, 2024)
This article mainly covers the aspects of Artificial Intelligence (AI) and its significance in the process of finding resolutions between parties in terms of international commercial disputes through arbitration courts. As pivotal as it sounds, this article additionally includes some data about advantages and disadvantages of Artificial Intelligence (AI). The writter discussed an abundance of prevalent topics in terms of Artificial Intelligence as a form of arbitrator in international arbitration courtrooms. Our readers could find an array of utilitarian information about the role of AI in the process of document review, fact-finding and award production. This article mostly provides a host of database regarding decision-making and provision of legal awards towards disputes occurred between parties from international agreements. The writer also included real life experiences of parties (countries,legal entities or individuals) and its effectiveness comparing to human-based court processes. By reading the article throughly, the readers are rewarded of getting many pertinent information regarding the legal consequences of utilization of AI in accordance with both international and national legislation of different countries.
Keywords: Artificial intelligence; e-commerce; international arbitration courts; arbitrators